Non-visible disease, the hidden disruptive experiences of chronic illness in adversity. Issue 1 (1st January 2020) - Estecha Querol, Sara; Clarke, Pam; Sattler, Elisabeth Lilian Pia; Halford, Jason C. G.; Gabbay, Mark
ABSTRACT: Objective : This study's principal aim was to describe the lived reality for people with cardiovascular disease (CVD) and other chronic health conditions, who live in economically deprived neighbourhoods in a city in North West England. Methodology : This is a qualitative, exploratory study based on in-depth, semi-structured interviews with participants experiencing compromised cardiovascular health, conducted in August 2017. The study sample comprised 14 adults (3 females) aged 54 to 76. Thematic analysis was used for data analysis, and the biographical disruption concept was used as theoretical reference to explore the results. Wider health inequalities literature supplemented the individual experiences of chronic illness. Results : Four main themes were developed from the data: (1) chronic illness as a disruptive experience; (2) struggling for money; (3) lifestyle and health risks; and (4) reflections on current inequalities. The varied nature of participants' narratives about their chronic illness indicated that the experience of biographical disruption depends on the wider socioeconomic and cultural factors of the individual. Discussion : This study suggests that biographical disruption theory combined with health inequalities contexts highlights the role of hidden suffering and enhances the understanding of chronic illness experiences and thus informs clinical management, service and public health planning.